Breaking The Link Between Legal Access To Alcohol And Motor Vehicle Accidents: Evidence From New South Wales. (15th June 2015) - Lindo, Jason M.; Siminski, Peter; Yerokhin, Oleg
Abstract: A large literature has documented significant public health benefits associated with the minimum legal drinking age in the USA, particularly because of the resulting effects on motor vehicle accidents. These benefits form the primary basis for continued efforts to restrict youth access to alcohol. It is important to keep in mind that policymakers have a wide variety of alcohol‐control options available to them, and understanding how these policies may complement or substitute for one another can improve policy making moving forward. Towards this end, we propose that investigating the causal effects of the minimum legal drinking age in New South Wales, Australia, provides a particularly informative case study, because Australian states are among the world leaders in their efforts against drunk driving. Using an age‐based regression discontinuity design applied to restricted‐use data from several sources, we find no evidence that legal access to alcohol has effects on motor vehicle accidents of any type in New South Wales, despite having large effects on drinking and on hospitalizations due to alcohol abuse. Copyright © 2015 John Wiley & Sons, Ltd.